The Effects of Familiarity on Oral Decoding Accuracy in an Oral Reading Task - Valle M., Alexsandria (My University, 2015)
The primary purpose of this study was to examine the relationship between the familiarity of the second reader on oral decoding accuracy in a choral reading task. Nine passages were obtained (three from each reading grade level: 4, 5, and 6). Three reading tasks were completed by each participant at their respective grade level. One task included reading aloud along with the audio-recording of an unfamiliar female voice. One task involved the participant reading along with an audio-recording of their mother and one task consisted of the participant reading aloud by themselves. Word reading accuracy and word reading rate data were collected. Results indicated that the participants read at a slower rate and less accurately when they read alone as compared to when they read along with their parents. This was interpreted as evidence supporting the importance of reading along with familiar individuals as compared to reading alone or along with unfamiliar voices.
I INTRODUCTION 1 | II LITERATURE REVIEW 3 | Normal Reading Processes 3 | Perceptual Analysis 4 | Word Recognition 4 | Word Reading’s Role in Reading Fluency 9 | Fluency Enhancement 10 | Rationale 11 III METHODS 13 | Participants 13 | Stimuli 13 Instrumentation 14 | Administration 14 | Data analysis 15 | IV RESULTS 17 | Decoding Accuracy 17 | V DISCUSSION 19 | Word Reading Accuracy 19 | Reading Rate 21 | Reading Fluency 23 | Limitations 23 | Recommendations 24 | REFERENCES 25 APPENDIX A: Institutional Review Board Approval Form 29 | APPENDIX B: Parental Permission Form 31 | APPENDIX C: Child Assessment Form 34 | APENDIX D: Experimental Reading Passages 36 |
Keywords: Communication Sciences and Disorders; Theses; Decoding; oral reading; oral decoding accuracy